Prediction of Pharmacokinetics Parameter and Molecular Docking Study of Antidiabetic Compounds from Syzygium polyanthum and Syzygium cumini - Widia Wati; Gunawan Pamudji Widodo; Rina Herowati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Syzygium polyanthum leaf extract and Syzygium cumini herbs extract have been reported to have antidiabetic activity. This study aimed to predict the molecular target of chemical constituents of S. polyanthum and S. cumini as well as study their interactions with various macromolecular targets of an antidiabetic agent. Molecular docking of all ligands was studied using the Autodock Vina program in PyRx, and the results are presented as binding affinity values (kcal/mol) of ligand against the protein. PyMOL is used to visualize the 3D molecular of docked conformation and ligand-protein interactions. The predicted pharmacokinetic parameters were obtained by SwissADME. Delphinidin-3-gentiobioside and isoquercitrin are predicted to have good interaction with DPP-4 and α-glucosidase, respectively. However, they are predicted to have poor absorption properties. Quercetin and kaempferol are predicted to have good interaction with PTP1B and glucokinase and showed good pharmacokinetic properties.